NOS2/ARG1 axis and immune cell ratios as promising prognostic and predictive biomarkers for Cetuximab combined with chemotherapy in wt-KRAS human colorectal cancer - Mataam, Djehane Houria; Galleze, Assia; Benkhelifa, Sarra; Trari, Ryad; Khelaifia, Wafa; Belhadef, Said; Bouhara, Sabrina; Ait Younes, Sonia; Benali, Anissa; Mahfouf, Hassan; Morales, Olivier; Belguendouz, Houda; et al. (Frontiers in Immunology, 2026)
BackgroundResistance to epidermal growth factor receptor monoclonal antibodies (anti-EGFR), such as cetuximab, remains a major therapeutic challenge. Growing evidence suggests that local tumor immune cells and systemic inflammation influence therapeutic outcomes. Our study aimed to investigate the balance between nitric oxide synthase-2 (NOS2) and arginase-1 (ARG1) expression and its association with immune contexture and clinical outcome in cetuximab-treated colorectal cancer patients.Methods100 patients with colorectal cancer (CRC) were included in this study. NOS2 and ARG1 expression and their metabolites were assessed using RT-qPCR, immunofluorescence, and biochemical assays. Tumor-infiltrating CD68+ pan-macrophages, CD163+ M2 like- macrophage, and CD8+ T cells were assessed using immunohistochemistry and immunofluorescence. Baseline complete blood counts were used to calculate systemic immune ratios, including the Neutrophil-to-Lymphocyte Ratio (NLR), Platelet-to-Lymphocyte Ratio (PLR), Monocyte-to-Lymphocyte Ratio (MLR), Systemic Immune-Inflammation Index (SII), and Systemic Inflammation Response Index (SIRI). Associations between NOS2/ARG1 profiles, systemic immune cell ratios, and treatment response were analyzed using Student’s t-test. Progression-free survival (PFS) and overall survival (OS) were estimated using Kaplan–Meier analysis.ResultsNOS2 and ARG1 levels were elevated in CRC, particularly in the late stages. Low NOS2/high ARG1 expression correlated with increased CD68+ and CD163+ cell infiltration, whereas high NOS2/lowARG expression was associated with increased CD8+ cell density. Systemic inflammatory indices were higher in patients with CRC than in controls. In mCRC patients receiving cetuximab plus chemotherapy, responders had lower NLR, SII, SIRI, and ARG levels and higher NO levels than non-responders. High baseline SII, SIRI, and ARG levels predicted poorer PFS and OS, whereas elevated NO levels predicted better outcomes. Interestingly, a combined score integrating NO, ARG, SII, and SIRI indicated a higher prognostic value than individual markers in mCRC patients.ConclusionOur study highlights the pivotal role of the NOS2/ARG1 axis in local immune infiltration, systemic inflammation, and clinical outcomes in mCRC patients receiving cetuximab. For the first time, we propose a novel combined score integrating NO, arginase, SII, and SIRI as simple, accessible, and non-invasive prognostic and predictive markers. Our findings may open new avenues for patient stratification and treatment optimization in precision oncology research.